Gamelan Reinvented: Cultural Sound Transformation in Membranophone Ensembles of East Java - Hidayatullah, Panakajaya; Simatupang, Gabriel Roosmargo Lono Lastoro; Setiawan, Aris; Livera, Kristen Angela (Institut Seni Indonesia Yogyakarta, 2024)
This study explores the phenomenon of pèghâ' in the musical traditions of terbhâng ghendhing and kemplang in Probolinggo and Bondowoso, which emerged as a response to past religious prohibitions on the use of metal gamelan instruments. The research focuses on uncovering the adaptation of metal gamelan music into the membranophone ensembles of terbhâng ghendhing and kemplang from a musicological perspective. Using qualitative approaches and ethnographic methods, data were collected through participant observation, in-depth interviews, and literature review. The findings reveal that elements such as kejhungan, drumming patterns, bonang patterns, and gending structures were preserved, although the shift from metal to membrane caused significant changes. These changes resulted in a playing style that is more repetitive, dynamic, and aligned with the membranophone's characteristics. This study also challenges the conventional view of membranophones as purely rhythmic instruments, demonstrating their capability to perform complex melodic roles in terbhâng ghendhing and kemplang. The process of pèghâ' underscores traditional music as a dynamic entity that continues to evolve through local creativity, creating new musical identities while maintaining its cultural roots.